SISTEM PENUNJANG KEPUTUSAN DALAM PENENTUAN RUTE DAN KAPASITAS MUATAN DISTRIBUSI DENGAN MENGGUNAKAN METODE SAVING MATRIX DAN NEAREST NEIGHBOAR PADA CV BINTANG BERKAH CIREBON - ., Nico Firmansyah; Lena Magdalena; Mesi Febima (Universitas Methodist Indonesia, 2024)
This research creates and designs a Decision Support System (SPK) for CV Bintang Berkah by combining the Saving Matrix and Nearest Neighbor methods to optimize the route and capacity of the distribution load. CV Bintang Berkah faces challenges in managing distribution costs and load capacity, which affects operational efficiency. The Saving Matrix method helps in determining distribution routes with distance and cost savings, while the Nearest Neighbor method optimizes the order of visits based on the closest distance. The implementation of this system is expected to reduce transportation costs, increase distribution efficiency, and improve service quality. This system uses PHP and MySQL, focusing on the Cirebon City and Regency areas. The results show that applying this method significantly reduces the distance and cost of distribution and increases efficiency in the distribution process. With this system, CV Bintang Berkah is expected to overcome distribution challenges better, save costs, and increase the company's profitability.